PERAN BIROKRASI KELEMBAGAAN DALAM PENERAPAN PENGENDALIAN HAMA TERPADU - Astuti, RR. Siti (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2015)
This study aimed to know the role of institutional bureaucracy in the implementation of integrated pest management. The study was conducted in April 2012 in central Java. IPM institutionalization efforts in Indonesia influenced by a lot of constraints such as constraints conceptual, institutional structures, program priorities, ego-sectoral and ego-discipline and empowerment of farmers. Strategies undertaken by the government is the institutionalization of plant protection, the development of management information systems, strengthening forecasting and observation, the provision of appropriate technology and site-specific duna, provision of protection and stabilization of pest control. The role of institutional bureaucracy in the implementation of IPM in central Java is not optimal because of weak cooperation and coordination among stakeholders as well as good organizational structure has not stabilized both central and local levels as a result of regional autonomy policy. Collaborative efforts and networks need both locally, nationally and globally. Cooperation and networking will provide additional information as a result of the activities of the exchange of information related to IPM.